Effectiveness of Parenting in Raising Parents' Awareness of Gadget Use in Children: Efektifitas Parenting Dalam Meningkatkan Kesadaran Orang Tua Terhadap Penggunaan Gadget Pada Anak - Andre, Lesis; Mustika Sari, Ayu; Marina (Journal of Vocational Education and Information Technology (JVEIT), 2024)
This research aims to determine the effectiveness of parenting in increasing parents' awareness of children's use of gadgets. The research method used is a qualitative method with a field study approach and data analysis using observation and interview techniques. The results of this research explain that parenting activities in increasing parents' awareness of children's use of gadgets make parents aware of the importance of supervision and positive parenting discipline towards their use. gadgets for children. Based on the results of interviews conducted by researchers with parents, it was explained that parenting patterns had changed towards being better in supervising children using gadgets. Parents have control, accompany the child and better understand the child's needs and participate in every child's activities, including accompanying the child if the child really needs a gadget. The parenting activities carried out produce synergy in the learning process at school and at home so that children can be more directed and controlled in using gadgets positively.